Dynamics of a single Condensing Two-Phase Bubble - A. Abdul-Majeed, Basma; B. Eliwy, Hussien (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The dynamics of a single condensing two-phase bubble of two different dispersed-continuous systems were studied. The systems were, CCl4 - water and CCl4 - 100% glycerol. Cinephotography was used to determine the change in height, diameter and time. These results were used to determine the experimental rise velocity of the bubble, which was compared with a theoretical one based on some equations used. It was found that the velocity of the first system remained almost constant, while it decreased gradually for the second system.